2024
DOI: 10.1002/aro2.47
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of poikilocytosis as an emerging erythrocytic biomarker for fish health assessment

Avishek Bardhan,
Thangapalam Jawahar Abraham,
Ratnapriya Das
et al.

Abstract: Fish health assessment is essential for maintaining sustainable aquatic ecosystems and ensuring the well‐being of wild and farmed fish populations. Hematological parameters are crucial indicators of fish health, with poikilocytosis emerging as a fundamental marker with significant diagnostic value. Poikilocytosis refers to abnormally shaped erythrocytes in bloodstream, reflecting underlying physiological and pathological conditions. Poikilocytosis can occur in various fish species and can be influenced by envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 217 publications
(288 reference statements)
0
1
0
Order By: Relevance
“…It was found that the PDGFB protein was distributed in red blood cells inside the blood vessel, germ cells, and Leydig cells in the seminiferous tubule space of the testes of Tibetan sheep at different developmental periods. As the most abundant circulating cells in the mammalian blood, red blood cells are essential for life and metabolism, and their main role is the transportation of oxygen via the circulatory system and the delivery of oxygen to organs and cells in the body including the reproductive system [ 21 , 22 , 23 ]. Also, red blood cells participate in the transport and delivery of nutrients through the circulating system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the PDGFB protein was distributed in red blood cells inside the blood vessel, germ cells, and Leydig cells in the seminiferous tubule space of the testes of Tibetan sheep at different developmental periods. As the most abundant circulating cells in the mammalian blood, red blood cells are essential for life and metabolism, and their main role is the transportation of oxygen via the circulatory system and the delivery of oxygen to organs and cells in the body including the reproductive system [ 21 , 22 , 23 ]. Also, red blood cells participate in the transport and delivery of nutrients through the circulating system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%